Knowledge and Protective Behaviors of Teachers on Skin Cancer: A Cross-Sectional Survey Study from Turkey - Celal Kus; Mine Mujde Kus; Hamit Sirri Keten; Huseyin Ucer; Numan Guvenc; Fatih Kus; Hasan Cagri Yildirim; Hatice Tuba Akbayram (MDPI AG, 2023)
Background: People socialize and receive education and training for the first time outside the home at school, where their teachers act as role models. Teachers play a crucial role in instilling sun-protection habits in children. Avoiding the sun between 10 a.m. and 4 p.m., staying in the shade, wearing sun-protective clothing, wearing sunglasses, wearing hats, using sunscreen products, and using an umbrella are some of the sun-protection methods described in the literature. This study sought to assess teachers' skin cancer knowledge and attitudes (SC). Methods: In this cross-sectional study conducted between 21 September 2020, and 21 October 2020, 647 teachers from 30 schools in Kahramanmaras were included with their consent. The number of teachers employed at Kahramanmaras was 1863. Accordingly, the sample was found to be 641 with a 5% margin of error and a 99% confidence interval. Schools were selected by a simple random method. Teachers' knowledge and behaviors were assessed using a 25-point questionnaire designed by the literature data to gauge the level of SC knowledge. Results: Of the 647 teachers included in this study, 230 (35.5%) were male, and 417 (64.5%) were female. The mean age of the participants was 38.44 ± 8.79 (min = 22, max = 65) years. The knowledge level of the teachers about SC was 13.54 ± 4.48 (min = 0, max = 23). The internet (75.9%) was the most preferred source of information. SC knowledge level was significantly higher in those with SC in their families and birthmarks on their bodies. (p < 0.001, p = 0.042, respectively). The rate of precaution taken to protect from the sun was higher in those with higher knowledge (p = 0.032). Women, primary school teachers, those with skin type 1, those with multiple nevi, and those with a high level of SC knowledge used statistically significantly more sunscreen (p = 0.001, p = 0.003, p < 0.001, p = 0.037, p = 0.002, respectively). Conclusions: It was found that the knowledge level of teachers about skin cancer and sun-protective behaviors was moderate. Correct behaviors increased as knowledge about SC grew. Information and recommendations made on the Internet should be made by experts. Additionally, health policymakers should implement projects aimed at improving teachers' knowledge and behaviors and, through them, teaching students about SC; as such projects would significantly contribute to both public health and health economics.